Researching Entrepreneurship Conceptualization and Design - Davidsson, Per (International Studies in Entrepreneurship,, 2016)
In this book, one of the most highly recognized entrepreneurship scholars shares in a personal and readable way his rich experience and ideas on how entrepreneurship can be researched. Entrepreneurship is a phenomenon of tremendous societal importance. It is also an elusive phenomenon, which makes researching it fun, fascinating-and frustrating at times. In this fully updated edition, numerous real examples accompany the treatment of problems and solutions concerning design, sampling, operationalization and analysis. Researching Entrepreneurship is targeted primarily at research students and academics who are relatively new to research or to entrepreneurship research. This said, basic knowledge of research methods is assumed, and when foundational issues are discussed they are typically approach from a non-standard angle and/or with an eye to illuminate entrepreneurship-specific problems and solutions. This makes large parts of the contents potentially valuable for entrepreneurship scholars at any level of research proficiency. The book is also of interest to sophisticated, non-academic users with a professional interest in collecting and analyzing data from emerging and young ventures, and to those who make use of published entrepreneurship research. For example, analysts in marketing research or consultancy firms, business associations, statistical agencies and other government offices may find this book to be a valuable tool. Moreover, while the examples are derived from entrepreneurship research, the book provides a unique "experienced empirical researcher" (rather than "textbook method expert") treatment of issues that are of equal relevance across the social sciences. This goes for topics like the role of theory; research design; validity assessment; statistical inference, and replication. Entrepreneurship research has developed rapidly in the decade that has passed since the first edition. Therefore, all chapters have been comprehensively updated and many have been extended; sometimes to twice the original length. Two of the original chapters have been excluded to make room for entirely new chapters on "the Dependent Variable" and "The Entrepreneurship Nexus." While retaining a unique, personal tone, the author uses examples and references that build on contributions from a large number of top entrepreneurship researchers.